Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1529/biophysj.105.072447
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Na+/Ca2+ Exchanger to Rapid Ca2+ Release in Cardiomyocytes

Abstract: Trigger Ca(2+) is considered to be the Ca(2+) current through the L-type Ca(2+) channel (LTCC) that causes release of Ca(2+) from the sarcoplasmic reticulum. However, cell contraction also occurs in the absence of the LTCC current (I(Ca)). In this article, we investigate the contribution of the Na(+)/Ca(2+) exchanger (NCX) to the trigger Ca(2+). Experimental data from rat cardiomyocytes using confocal microscopy indicating that inhibition of reverse mode Na(+)/Ca(2+) exchange delays the Ca(2+) transient by 3-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 71 publications
(128 reference statements)
2
52
0
Order By: Relevance
“…This measurement is a rudimentary proof-of-principle test for how effectively a Ca 2+ wave-front can sensitize the RyRs in the CRU via increased SR Ca 2+ load (Keller et al 2007). The distance between the CRUs in the longitudinal direction was ∼2 μm and with a Ca 2+ wave travelling at 100 μm s −1 (Lamont et al 1998;Ter Keurs & Boyden, 2007) (Trafford et al 1995;Lines et al 2006) NCX exists within the dyad where it would experience a very high local [Ca 2+ ]. We hypothesized that including NCX flux within the dyad would be capable of directly and markedly altering dyadic [Ca 2+ ], and spark dynamics.…”
Section: Mathematical Modelmentioning
confidence: 94%
See 1 more Smart Citation
“…This measurement is a rudimentary proof-of-principle test for how effectively a Ca 2+ wave-front can sensitize the RyRs in the CRU via increased SR Ca 2+ load (Keller et al 2007). The distance between the CRUs in the longitudinal direction was ∼2 μm and with a Ca 2+ wave travelling at 100 μm s −1 (Lamont et al 1998;Ter Keurs & Boyden, 2007) (Trafford et al 1995;Lines et al 2006) NCX exists within the dyad where it would experience a very high local [Ca 2+ ]. We hypothesized that including NCX flux within the dyad would be capable of directly and markedly altering dyadic [Ca 2+ ], and spark dynamics.…”
Section: Mathematical Modelmentioning
confidence: 94%
“…Both computational and experimental studies have also investigated whether NCX can contribute to EC coupling (Lines et al 2006;Larbig et al 2010). Here we used our model to predict the amount of Ca 2+ that can be extruded from the CRU via NCX during a spark.…”
Section: + Concentration During a Sparkmentioning
confidence: 99%
“…One possible source of the reduced Na ϩ mobility is the dyadic cleft itself (42), in which a restricted space reduces the effective diffusional coefficient. In neonatal rabbit myocytes, electron micrographs have identified 300-nm sheets of the SR membrane located ϳ20 nm beneath the sarcolemma (32), which may contribute to reduce Na ϩ mobility.…”
Section: Contribution Of Na ϩ Channels To Reverse-mode Ncxmentioning
confidence: 99%
“…Coupling between NCX and RyR at early stages in development may benefit from the presence of ϳ300-nm-wide sheets of the subsarcolemmal SR membrane recently identified in 3-day-old, but not 56-day-old, ventricular myocytes (32) The stoichiometry of NCX transport renders the reversal potential of NCX intensely sensitive to cytosolic Na ϩ concentration, and small changes in global Na ϩ concentration are expected to mediate large changes in I NCX (20). In fact, modeling experiments have reported that a solitary Na ϩ channel could be sufficient to induce reverse-mode NCX in a dyadic cleft if the influx is concomitant with greatly reduced Na ϩ mobility (42). Thus, Na ϩ channels localized within localized clusters of NCX are expected to have important functional consequences.…”
mentioning
confidence: 99%
“…The physiological role of NCE is to maintain low intracellular Ca 2+ concentration at rest by extruding excess intracellular Ca 2+ in inward mode after the fast Ca 2+ -induced Ca 2+ release (CICR) process during systole. On the other hand, Ca 2+ influx via the outward mode of NCE may also contribute to the trigger Ca 2+ and may quicken, enhance or even provoke myocytes contraction [7]. Increases in NCX mRNA and protein are common findings in several animal models of heart failure or left ventricular hypertrophy [8][9][10], as well as in similar cardiac disorders in man [11,12].…”
Section: Introductionmentioning
confidence: 99%